Effect of pre-strain on mechanical properties of low carbon steel - Muhamad Saiful Zakwan, Ramlan (2012)
This project is about to study the effect of pre-strain on mechanical properties of low carbon steel. The objectives for this project are to differentiate the influence of various pre-strain on mechanical properties of low carbon steel. This project involves analysis of the mechanical properties of low carbon steel. From the material composition test done, the material that are used is low carbon steel AISI1018. Investigate the influence of pre-strain on the mechanical properties and fitness-for-service of the low carbon steel pipeline subjected to large plastic deformation. Axial tensile pre-strains of 1.5, 5 and 10% were applied to bar-type tensile specimens extracted from the longitudinal direction of the pipe body prior to mechanical testing. Tensile test results revealed that yield strength and tensile strength increased with increasing tensile pre-strain. The rate of increase of the yield strength was greater than that of the tensile strength. The engineering and true stress–strain curves of the virgin and pre-strained materials at room temperature. There was no difference between the virgin material and the pre-strain material in the elastic region; however, strain hardening decreased with increased prestrain in the plastic zone. Increasing pre-strain increased yield strength but decreased the strain to fracture. The difference in fracture strain between the virgin and pre-strained materials corresponded to the amount of pre-strain applied prior to the tensile tests.